“BIOESTIMULANTES COMERCIALES DE ORIGEN ORGÁNICO E INORGÁNICO EN BROTES DE Musa AAB (PLATANO CV. HARTON) PROPAGADOS EN CAMARAS TERMICAS.” - Moreno Chapiliquin, Elian Fernando (2024)
The cultivation of Musa AAB (plantain cv. Hartón) is of economic relevance and food security in Latin America, being a tropical product of great importance. Biostimulants play a crucial role in the regulation of processes ranging from the growth and development of banana plants.The objective of this research was to evaluate the effect of commercial biostimulants of organic and inorganic origin on shoots of Musa AAB (plantain cv. hartón) propagated in thermal chambers.